Hva kan vi lære av TALIS 2018? (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
" What are the specific challenges that teachers and school leaders face, and how do they feel about their working conditions? These are among the themes of the international TALIS study. The authors of this book take a close look at the 2018 survey that was carried out in 48 countries, including all of the Nordic countries.